Singular value decomposition of received ultrasound signal to separate tissue, blood flow, and cavitation signals. (30th May 2018) - Ikeda, Hayato; Nagaoka, Ryo; Lafond, Maxime; Yoshizawa, Shin; Iwasaki, Ryosuke; Maeda, Moe; Umemura, Shin-ichiro; Saijo, Yoshifumi
Abstract: High-intensity focused ultrasound is a noninvasive treatment applied by externally irradiating ultrasound to the body to coagulate the target tissue thermally. Recently, it has been proposed as a noninvasive treatment for vascular occlusion to replace conventional invasive treatments. Cavitation bubbles generated by the focused ultrasound can accelerate the effect of thermal coagulation. However, the tissues surrounding the target may be damaged by cavitation bubbles generated outside the treatment area. Conventional methods based on Doppler analysis only in the time domain are not suitable for monitoring blood flow in the presence of cavitation. In this study, we proposed a novel filtering method based on the differences in spatiotemporal characteristics, to separate tissue, blood flow, and cavitation by employing singular value decomposition. Signals from cavitation and blood flow were extracted automatically using spatial and temporal covariance matrices.